2013
DOI: 10.1057/jam.2013.11
|View full text |Cite
|
Sign up to set email alerts
|

Breaking into the blackbox: Trend following, stop losses and the frequency of trading – The case of the S&P500

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. In this paper we compare a variety of technical trading rules in the context of investing in the S&P500 index. These rules are increasingly popular both among retail investors and CTAs and similar investment funds. We find that a range of fairly simple rules, including the popular 200-day moving average trading rule, dominate the long only, passive investment in the index. In particular, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 26 publications
4
18
1
Order By: Relevance
“…Clare et al (2013) also showed that the 10-month calculation period for the average is not critical to their results. They found that 6-, 8-, 10-, and 12-month calculation rules produce very similar results.…”
Section: Editor's Notementioning
confidence: 99%
“…Clare et al (2013) also showed that the 10-month calculation period for the average is not critical to their results. They found that 6-, 8-, 10-, and 12-month calculation rules produce very similar results.…”
Section: Editor's Notementioning
confidence: 99%
“…Consistent with Faber (2007), no short-selling is permitted and no transactions costs are deducted. As mentioned, Clare et al (2013) examined whether more complex technical trading rules, stoplosses or more frequent trading would improve performance but they show conclusively that this is not the case so we have stuck with the straightforward model.…”
Section: Trend Following Strategymentioning
confidence: 98%
“…There are a very large number of ways of defining a 'trend' and these have been explored extensively in the investing literature: one can look at today's asset price and compare it with an average of the last 90, 120, or 200-day averages (so-called 'moving averages'), or compare different moving averages to see when (if) they 'crossover' , or one could simply ask if recent (however defined) returns are positive. Clare et al (2013) investigate a very wide range of such technical rules for investing in the S&P 500 for most of the 20 th century and conclude that very simple trend-following investing rules are at least as good as, if not superior to, more complex rules.…”
Section: Benefits Of Using Automated Trading Rulesmentioning
confidence: 99%
“…Consistent with Faber (2007), no short-selling is permitted and no transactions costs are deducted. Clare et al (2013) examine whether more complex technical trading rules, stop-losses or more frequent trading would improve performance but they show conclusively that this is not the case.…”
Section: Trend Following Portfoliosmentioning
confidence: 99%
“…Essentially investors are looking to own assets In this paper we apply the simple rule used by Faber (2007) and which has been extensively tested and discussed in Clare et al (2013) If the price of the asset class index is above its 10-month moving average then we classify the asset class as in an uptrend and it is purchased, if not already held. However, if the price is below the 10-month moving average then the asset is classified as in a downtrend and the asset is sold with the proceeds invested in US Treasury Bills.…”
Section: Trend Following Portfoliosmentioning
confidence: 99%